Left atrial anatomical variations correlate with atrial fibrillation sources near the left atrial ridge. (19th May 2022) - Gagyi, R; Szegedi, N; Simon, J; Wijchers, S; Bhagwandien, R; Kong, M; Ruppersberg, P; Szili-Torok, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Anatomical variations and characteristics of the left atrium (LA) may have a previously undescribed effect on source locations in atrial fibrillation (AF). Electrographic flow (EGF) mapping is a novel method used to estimate cardiac action potential flow in the atria that can detect AF sources in patients with persistent AF. The EGF technology offers a revolutionary mapping possibility for AF, however, it is not commercially available yet. Purpose: This is the first study aiming to investigate the relationship between anatomical characteristics of the LA and non-PV sources detected by EGF in patients with persistent AF. Methods: We collected cardiac computed tomography (CT) and EGF data from patients who underwent radiofrequency catheter ablation (CA) for persistent AF. EGF mapping creates a spatial and temporal reconstruction of electric potentials derived from endocardial unipolar electrograms. By analyzing EGF maps obtained during CA procedures, we localized non-PV sources in the LA. Patients with individual stable sources with a source activity above threshold (leading source present in more than > 26% of the time) were classified as having an S-Type EGF signature with source-dependent AF. Patients with no stable active source pattern and no leading source with a source activity above threshold were characterized as having a C-Type EGF signature consistent with source-independent AF. We assessed LA anatomical characteristics including size, LAA length, LAA ostial diameter, trajectory of the left superior pulmonary vein (LSPV) and its relation to the LAA on cardiac CT scans. Abutting LAA-LSPV was defined as cases when the LSPV touched the posterior aspect of LAA, and the maximal distance between the two structures was less than 2 mm. Those cases where the distance between LAA and LSPV was more than 2 mm were defined as non-abutting LAA-LSPV. Results: Thirty patients were included in this study (mean age 62.4±6.8 years):23 patients had an S-Type EGF signature (77%), and 7 patients had a C-Type EGF signature (23%). We identified 10 patients with AF sources near the LA ridge, while twenty patients had no leading source near the LA ridge. LA anatomical characteristics, LAA length and ostial diameter showed no correlation with the presence of a leading source near the ridge. We described 19 patients with abutting LAA-LSPV, and 11 patients with non-abutting LAA-LSPV. Three out of 19 patients presented with a leading source near ridge in the abutting LAA-LSPV group, while 7 out of 11 patients presented with a leading source near ridge in the non-abutting LAA-LSPV group (p=0.01). Conclusion: Our data suggests that non-abutting LAA-LSPV is associated with the presence of AF sources near the LA ridge.